Asuhan Keperawatan Gerontik Pada Pasien Insomnia Dengan Masalah Keperawatan Gangguan Pola Tidur Menggunakan Terapi Relaksasi Otot Progresif di UPT PSTW Kabupaten Jombang - Luisa Wijaya Suryaning Ayu; Tiara Fatma Pratiwi; Dina Camelia; Faishol Roni; Arif Wijaya (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract Insomnia is a sleep disorder, difficulty maintaining sleep patterns and very poor sleep quality experienced by individuals, if not controlled properly it will cause sleep pattern disorders. If this is not treated, it can cause various complications. This study aims to carry out gerontic nursing care for insomnia clients with sleep pattern disorders using progressive muscle relaxation therapy. The design of this research is a case study with a nursing process approach on 2 clients with the same illness and nursing problems for 7 consecutive days. The results of the study showed that after nursing care there was a decrease in the scale of sleep patterns before progressive muscle relaxation therapy was carried out, it was 5 and after progressive muscle relaxation therapy it decreased to 1 on day 7. The conclusion of this study is that Progressive Muscle Relaxation therapy can be used as a non-pharmacological therapy for Prevent a decrease in sleep quality in insomnia patients. It is hoped that the results of this case study will be useful as additional theory and additional material for providing non-pharmacological nursing actions in overcoming sleep pattern disorders using progressive muscle relaxation therapy in insomnia patients with sleep pattern problems. Keywords: Elderly, Insomnia, Sleep Pattern Disorders, Progressive Muscle Relaxation.